Quantifying the extremity of windstorms for regions featuring infrequent events. (July 2017) - Walz, Michael A.; Kruschke, Tim; Rust, Henning W.; Ulbrich, Uwe; Leckebusch, Gregor C.
Abstract: This paper introduces the Distribution‐Independent Storm Severity Index (DI‐SSI). The DI‐SSI represents an approach to quantify the severity of exceptional surface wind speeds of large scale windstorms that is complementary to the SSI introduced by Leckebusch et al . While the SSI approaches the extremeness of a storm from a meteorological and potential loss (impact) perspective, the DI‐SSI defines the severity in a more climatological perspective. The idea is to assign equal index values to wind speeds of the same singularity (e.g. the 99th percentile) under consideration of the shape of the tail of the local wind speed climatology. Especially in regions at the edge of the classical storm track, the DI‐SSI shows more equitable severity estimates, e.g. for the extra‐tropical cyclone Klaus. In order to compare the indices, their relation with the North Atlantic Oscillation is studied, which is one of the main large scale drivers for the intensity of European windstorms. Abstract : In order to quantify the extremity of European winter windstorms, the Distribution‐independent Storm Severity Index (DI‐SSI) was developed which accounts for the shape of the tail of the local wind speed distribution. This index represents an extension to the SSI developed by Leckebusch et al . Being of parametric nature, the DI‐SSI shows more coherent areas of intensity and an improved correlation with the North Atlantic Oscillation especially at the edges of the classic Atlantic storm track.